PENGARUH PENGALOKASIAN DANA SEKOLAH TERHADAP PENYELENGGARAAN PENDIDIKAN INKLUSIF - Angre Claudia Nasution; Asep Supena; Salmatus Saadah Putri; Septiana Dwiningrum (JIPD (Jurnal Inovasi Pendidikan Dasar), 2021)
Abstract: Maximum inclusive education can be seen from good management for the school. One of them is financial management/funding. Funding and the allocation of these funds are one of the influential aspects for the success of schools in implementing inclusive education. So that this study aims to determine the effect of the allocation of school funds at SMA Garuda Cendekia Jakarta. This study uses a qualitative descriptive method with interview techniques with one of the special supervisor teachers (GPK) who has been teaching for at least 5 years. The results showed that Garuda Cendekia High School needed sufficient funds to implement inclusive education because the management and funding at Garuda Cendekia High School had not been maximized, especially related to special facilities for children with special needs.